PENGARUH PENERAPAN TEKNIK SEPAK BOLA VERBAL DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 18 SIJUNJUNG - Sastridani, Sastridani; K, Delsi; Febriana, Rina (Pendidikan Matematika, 2013)
The research was motivated by the lack of understanding of mathematical concepts students at SMP 18 Sijunjung, one attempt to do is to apply the technique with verbal football quiz. This study aims to determine how the development of students understanding of mathematical concepts during the learning process using the technique of verbal football with quizzes and whether students understanding of mathematical concepts by applying techniques accompanied verbal quiz football better than the students understanding of mathematical concepts using conventional learning. This type of research is experimental research on the subject with a random design. The population in this study were students of class VIII. Class is class VIII.A sample as the experimental class and the control class VIII.B class. Instruments used in the study were quizzes and final test and the test used is a form of essay with reliability = 0.90. Data analysis technique is to use a one-way t-test, with , so it can be concluded that the students understanding of mathematical concepts using verbal techniques accompanied quiz football better than the students understanding of mathematical concepts by using conventional learning.